Immunogenicity and Safety of Yellow Fever Vaccine in Allogeneic Hematopoietic Stem Cell Transplant Recipients After Withdrawal of Immunosuppressive Therapy. (26th October 2017) - Sicre de Fontbrune, Flore; Arnaud, Cécile; Cheminant, Morgane; Boulay, Aude; Konopacki, Johana; Lapusan, Simona; Robin, Christine; Bernaudin, Françoise; Suarez, Felipe; Simon, François; Socié, Gérard; Colin de Verdière, Nathalie; et al.
Abstract : Yellow fever (YF) vaccine appears safe and immunogenic in selected hematopoietic stem cell transplant recipients. Persistent immunity to YF vaccine is observed in some patients vaccinated before transplantation and/or vaccinated with an immunized donor. Immunity to YF should be evaluated prior to vaccination. Abstract: As a live attenuated vaccine, yellow fever vaccine (YFV) is not routinely performed after allogeneic hematopoietic stem cell transplant (HSCT) despite it being the only efficient preventive therapy. We retrospectively identified 21 HSCT recipients immunized with YFV at a median of 39 months after HSCT and a median of 33 months after withdrawal of immunosuppression without any side effects. Eighteen evaluable patients had protective immunity after YFV. We also observed that a third of the recipients vaccinated with YFV before HSCT had persistent protective immunity after HSCT.